SAPS: semantic atompub-based services - Lanthaler, Markus; Guetl, Christian (CPS, 2011)
The utopian promise of a uniform service landscape in the form of SOAP, WSDL, and UDDI made by service oriented architectures (SOA) built on Web services has proven elusive. Instead more and more prominent Web service providers opted to expose their services based on the REST architectural style. Nevertheless there are still problems on formal describing, finding, and orchestrating RESTful services. While there are already a number of different approaches, none so far has managed to break out of its academic confines. Thus, we propose a novel approach to build Semantic RESTful Services based on proven technologies. The combination of those proven technologies leads to scalable and loosely coupled systems and has the additional advantage, that developers are already familiar with its functioning.